Reliability and validity of the Parent Efficacy for Child Healthy Weight Behaviour (PECHWB) scale - Palmer, F.; Davis, Melissa (Blackwell Scientific Publications, 2014)
Background Interventions for childhood overweight and obesity that target parents as the agents of change by increasing parent self-efficacy for facilitating their child’s healthy weight behaviours require a reliable and valid tool to measure parent self-efficacy before and after interventions.Nelson and Davis developed the Parent Efficacy for Child Healthy Weight Behaviour (PECHWB) scale with good preliminary evidence of reliability and validity. The aim of this research was to provide further psychometric evidence from an independent Australian sample.Methods Data were provided by a convenience sample of 261 primary caregivers of children aged 4–17 years via an online survey. PECHWB scores were correlated with scores on other self-report measures of parenting efficacy and 2- to 4-week test–retest reliability of the PECHWB was assessed.Results The results of the study confirmed the four-factor structure of the PECHWB (Fat and Sugar, Sedentary Behaviours, Physical Activity, and Fruit and Vegetables) and provided strong evidence of internal consistency and test–retest reliability, as well as good evidence of convergent validity.Conclusion Future research should investigate the properties of the PECHWB in a sample of parents of overweight or obese children, including measures of child weight and actual child healthy weight behaviours to provide evidence of the concurrent and predictive validity of PECHWB scores.